Implementasi Pendekatan Saintifik Pada Pembelajaran Cinta Lingkungan Pendidikan Anak Usia Dini (Paud) Di Kabupaten Wonosobo - Munawaroh, Hidayatu; Retyanto, Banar Dwi (Al-Athfal: Jurnal Pendidikan Anak, 2016)
The purpose of this study is to describe the application of a scientific approach to learning to love the environment of early childhood education (ECD) in Wonosobo regency. This study uses qualitative research directed towards field research. Data were collected through interviews, observation and documentation as well as coding into the record interviews, field notes, and notes documentation. The data were analyzed descriptively and qualitatively by using an interactive model. The results showed that the application of the scientific approach carried out through five stages or activities include (1) observe is presenting objects or real objects of the themes discussed to be observed by a child with all the senses, (2) ask that provides the opportunity for all children to inquire matters interesting things to know their curiosity about a topic of discussion, (3) to gather information is to do a simple experiment to prove the questions asked by children and collect information about the topics discussed on a variety of sources, (4) reasoning is discussed to make inferences about the topics discussed and combines the knowledge that has been owned subsidiary with newly acquired knowledge, (5) communicating that communicate the knowledge acquired either through language, stories and works.